In-vitro Nutritional Assessment of Soy Nuggets based Dog Food - Kaur, Mohneet (Indian Journal of Animal Nutrition, 2021)
The present study was conducted to evaluate the effect of different processing techniques on nutritive value and to determine appropriate inclusion level of soy nuggets (SN) in dog food. Standardized diets were subjected to different processing techniques viz. raw, boiling and extrusion. The in-vitro study was performed with two incubation stages, with gastric phase of 2 hours in the presence of pepsin, gastric lipase in HCl solution, and intestinal phase of 4 h in presence of pancreatin and bile salts in buffer solution. Data analysis revealed that extrusion improved (P